Insult Politics: Donald Trump, Right-Wing Populism, and Incendiary Language - Oscar Winberg (European Journal of American Studies)
While often hailed—or denounced—as unprecedented, the 2016 presidential campaign of Donald Trump was not ahistoric. This article positions the Trump campaign in historical traditions of right-wing populism, incendiary political language, and insulting rhetoric. Trump’s mocking and insulting rhetoric in the campaign was widely described as both norm-breaking and, surprisingly, not politically harmful. This article challenges both assumptions, illustrating how Trump fits into a long tradition of insult politics, and how it remains controversial and politically dangerous. The insult politics Trump utilized throughout his campaign served a political purpose. However, there are strong indications that Trump won the White House in spite of his mocking rhetoric, not because of it. Rather, the particular political position of Trump, and his media image, explains how he could utilize insult politics to his advantage. The initial unwillingness of the other candidates to engage in insult politics, as well as the backlash against those who eventually did, further illustrates the problems inherent in the use of insulting and mocking language.